The extent of compliance with FRS 101 standard: Malaysian evidence - Abdul Rahman, Azhar; Hamdan, Mohd Diah (Emerald Publishing Limited, 2017)
Purpose: The purpose of this paper is to investigate Malaysian companies' compliance with mandatory accounting standards.Specifically, this study examines the efficacy of agency-related mechanisms on the degree of compliance with Financial Reporting Standards (FRS) 101, Presentation of Financial Statements.It so proceeds by focussing on corporate governance parameters (board characteristics and ownership structure) and other firm characteristics. Design/methodology/approach: Using data drawn from a sample of 105 Malaysian companies listed on the ACE market in 2009, the authors employ multiple regression analysis models to establish whether selected corporate governance and company-specific characteristics (proxying for agency-related mechanisms) are related to the degree of disclosure compliance.Findings: The results indicate that the overall disclosure compliance is high (92.5 per cent).Furthermore, only firm size is positively associated with the degree of compliance.The other variables, those consisting of board independence, audit committee independence, CEO duality, the extent of outside blockholders' ownership and leverage, do not show any significant relationship with the degree of compliance. Research limitations/implications: This study focusses on only one accounting standard (FRS 101) that is mandatory in Malaysia. FRS 101 is both structured and rigid, leaving no room for companies to conceal any particular information.The sample of Malaysian companies selected is restricted to those listed only on the ACE market.As such, the results cannot be generalised to every company in Malaysia. Practical implications: These results have important implications for policy makers because they suggest that whilst agency-related mechanisms may motivate compliance with mandatory standards, full compliance may be unattainable without regulations.Originality/value: This is the only study in Malaysia to investigate the impact of regulatory requirements on corporate compliance level by companies listed on the new ACE market, which was introduced by the Bursa Malaysia in August 2009.This study contributes to the literature by examining the effects of both company-specific characteristics (such as company size, company age, liquidity, etc.) and corporate governance parameters on the degree of corporate compliance with mandatory disclosure, simultaneously, in contrast with prior studies which have examined them in isolation.